Anti-HIV-1 Protostane Triterpenes and Digeranylbenzophenone from Trunk Bark and Stems of Garcinia speciosa - Vatcharin Rukachaisirikul (2018)
Three new protostanes, garciosaterpenes A (1), B (2) and C (3), together with a new digeranylbenzophenone, garciosaphenone A (4) were isolated from the ethyl acetate fractions obtained from the crude methanol extracts of the trunk bark and stems of Garcinia speciosa. The structures were elucidated by spectroscopic methods and chemical reactions. Compounds 1 and 3 showed significant inhibitory activities (IC50 15.5 and 12.2 μg/ mL, respectively) against HIV-1 reverse transcriptase and in the syncytium assay (EC50 5.8 μg/mL with T1 3.4 and 37.0 μg/mL with TI 1.9, respectively). Compound 4 was active in HIV-1 RT assay (IC50 23.9 μg/mL), but toxic in the syncytium assay. This work represents the first report on the anti-HIV-1 activities of the protostane triterpenes.